Singapore English : structure, variation, and usage - Leimgruber, Jakob R. E. (Jakob Robert Eugen), 1980- (Cambridge : Cambridge University Press, 2013)
'In recent years the study of English and its global varieties has grown rapidly as a field of study. The English language in Singapore, famous for its vernacular known as'Singlish', is of particular interest to linguists because it takes accent, dialect and lexical features from a wide range of languages including Malay, Mandarin, Hokkien and Tamil, as well as being influenced by the Englishes of Britain, Australia and America. This book gives a comprehensive overview of English in Singapore by setting it within a historical context and drawing on recent developments in the field of indexicality, world Englishes and corpus research. Through application of the indexicality framework Jakob Leimgruber offers readers a new way of thinking about and analysing the unique syntactic, semantic and phonological structure of Singapore English. This book is ideal for researchers and advanced students interested in Singapore and its languages.'--Publisher's website.
Introduction: Singapore and its Englishes -- Variation in Singapore English: old and new models -- Description: phonology and lexicon -- Description: grammar -- Indexicality: a model for Singapore? -- Conclusion: the variety as a structural unit.
Includes bibliographical references (page 134-145) and indexes.
Keywords: English language -- Singapore; English language -- Variation -- Singapore; English language -- Social aspects -- Singapore; Language and culture -- Singapore; Singapore -- Languages